RUANG SAKRAL DAN PROFAN DALAM ARSITEKTUR MASJID AGUNG DEMAK, JAWA TENGAH - Dwindi Ramadhana; Atyanto Dharoko (Universitas Negeri Yogyakarta, 2018)
ABSTRACTDemak Great Mosque is a mosque of historical heritage during the Islamic kingdoms in the 14th century. Until now, this mosque still has an important share for the community as a place of religious worship and considered sacred. Against this background and the social conditions of society have developed, there is an indication that the Great Mosque of Demak has its own meaning on the spaces within the mosque-related to sacred and profane. The purpose of this research is to identify the sacred and profane space in the architecture of the Grand Mosque of Demak and identify the factors that influence the formation of the properties of the space. This research uses rationalistic approach and deductive qualitative method. The result of this study reveals that in its use, the spaces at the Great Mosque of Demak are divided into a room that is not worldly (sacred) and the room that is worldly (profane). Space that is (not worldly) is liwan and pawestren. While the worldly room is pawestren and porch. Factors affecting the sanctity of space are physical barriers and holiness of worship space. While sanctity becomes a legitimate requirement of worship activities, so it becomes the main requirement of the sacred or not a place.Keywords: Demak, Mosque, Profane, Sacred ABSTRAKMasjid Agung Demak adalah masjid warisan sejarah selama kerajaan Islam di abad ke-14. Hingga saat ini, masjid ini masih memiliki andil penting bagi masyarakat sebagai tempat ibadah dan dianggap sakral. Dengan latar belakang ini dan kondisi sosial masyarakat telah berkembang, ada indikasi bahwa Masjid Agung Demak memiliki maknanya sendiri di ruang-ruang di dalam masjid yang berkaitan dengan sakral dan profan. Tujuan dari Kajian ini adalah untuk mengidentifikasi ruang sakral dan profan dalam arsitektur Masjidil Haram dan mengidentifikasi faktor-faktor yang mempengaruhi terbentuknya sifat ruang. Kajian ini menggunakan pendekatan rasionalistik dan metode kualitatif deduktif. Hasil Kajian ini mengungkapkan bahwa dalam penggunaannya, ruang di Masjid Agung Demak terbagi menjadi ruangan yang tidak bersifat duniawi (sakral) dan ruangan yang bersifat duniawi (profan). Ruang yang (bukan duniawi) adalah liwan dan pawestren. Sedangkan ruang duniawi adalah pawestren dan serambi. Faktor-faktor yang mempengaruhi kesucian ruang adalah penghalang fisik dan kesucian ruang ibadah. Sedangkan kesucian menjadi kebutuhan ibadah yang sah, sehingga menjadi kebutuhan utama yang sakral atau bukan tempat.Kata kunci: Demak, Masjid, Profane, Sakral